Antenna motion errors in bistatic SAR imagery. (6th May 2015) - Wang, Ling; Yazıcı, Birsen; Yanik, H Cagri
Abstract: Antenna trajectory or motion errors are pervasive in synthetic aperture radar (SAR) imaging. Motion errors typically result in smearing and positioning errors in SAR images. Understanding the relationship between the trajectory errors and position errors in reconstructed images is essential in forming focused SAR images. Existing studies on the effect of antenna motion errors are limited to certain geometries, trajectory error models or monostatic SAR configuration. In this paper, we present an analysis of position errors in bistatic SAR imagery due to antenna motion errors. Bistatic SAR imagery is becoming increasingly important in the context of passive imaging and multi-sensor imaging. Our analysis provides an explicit quantitative relationship between the trajectory errors and the positioning errors in bistatic SAR images. The analysis is applicable to arbitrary trajectory errors and arbitrary imaging geometries including wide apertures and large scenes. We present extensive numerical simulations to validate the analysis and to illustrate the results in commonly used bistatic configurations and certain trajectory error models.